Potencial de aplicação e otimização de técnicas de desenvolvimento de baixo impacto na gestão de águas pluviais urbanas - Froemming, Gabriel Herbstrith (2019)
Low Impact Development (LID) techniques focus on the implementation of decentralized structures for stormwater control. However, the effects of its implementation on the basin scale are still poorly understood. This work aimed to evaluate the potential of implementing LID structures through a simulation-optimization approach, using the SWMM Model. Additionally, a multiobjective optimizer algorithm (NSGA-II) was used to find optimal implementation solutions. The area of study adopted is an urban basin of approximately 5 squared quilometers, the Arroio Cancela basin, located in the municipality of Santa Maria-RS, Brazil. The current and future occupation conditions were also analyzed, evaluating the watershed runoff conditions. Pre-occupation, current and future occupation scenarios were evaluated, in addition to proposing three types of LID: Green Roofs, Bioretention and Combination of the two structures, considering implementation of 100 %, 50 % and 25 %. The algorithm seek optimal solutions for LID implementation by distributing in the sub-basins to minimize cost and peak flow (Qp) simultaneously. Comparing current and post-development scenarios, results found an increase by 6.7 % to 46.3 % for Qp and 14.2 % to 50.4 % for volume. The largest increases were for lower intensity events, equalizing Qp at higher intensity events, indicating an temporal increase of critical runoff events in the basin. In the simulation of the LIDs scenarios, the results showed an incremental increase with the percentage of structures implementation in the basin, saving up to 45 % for lower intensity events, 29 % for TR 10 and 17 % for larger intensities. Comparing the implementation percentage, the scenarios 100 %, 50 % and 25 % maximum and reduced Qp reduction values from 6 % to 45 %, 0 % to 32 % and 0 % to 26 %, respectively. Comparing the LID scenarios in terms of cost-benefit ratio, Combinado showed the most efficiency, with Bioretention alone showing the least efficient and lowest execution cost (up to R$23 million), while Green Roof has the highest cost, up to R$ 160 Million. The combined scenario showed costs of up to R$ 100 million. In the optimized solutions the combined scenario were considered the most cost-effective. With regard to optimizing the distribution of LIDs in the basin, the most costeffective solutions implemented LID in the more upstream urbanized basins, so drainage improvement efforts can prioritize these locations. LID scenarios can reduce performance control performance. However, efficiciency is reduced with the increase of return time of the events. An optimized potential and cost-benefit analysis allows the assessment of effectiveness of LIDs in solving urban drainage problems, as well as be evaluated in comparison with traditional drainage solutions.